Philosophy in the Islamic World : A Very Short Introduction - Adamson, Peter, 1972- (Oxford Oxford University Press, 2015)
In this introduction, Peter Adamson sheds light on the philosophical ideas that emerged in the Islamic world. From the beginnings of the tradition to the twenty first century, he traces the history of philosophy among those living in Islamic lands, highlighting its key themes and ongoing relevance to contemporary concerns.
Include Index
Keywords: Islamic philosophy